Body Dissatisfaction Pada Wanita Masa Emerging Adulthood: Bagaimana Peranan Social Comparison dan Perfeksionisme - Aliffia Ananta; Suhadianto Suhadianto (Psikostudia : Jurnal Psikologi, 2022)
Women in emerging adulthood experience a variety of physical and psychological changes and developmental tasks. The existence of various exposures to the mass media, environment, and family makes women compare themselves with others and socially. Doing social comparisons and perfectionism has the risk of making individuals experience body dissatisfaction. This study aims to determine the relationship between social comparison and perfectionism with body dissatisfaction. The participants of this study were 350 women in emerging adulthood who were taken using Conveniance Sampling. This research instrument was adapted from the Iowa-Netherlands Comparison Orientation Measure (α=0.909), Frost Multidimensional Perfectionism Scale (α=0.857), and body dissatisfaction scale (α=0.911) compiled by researchers based on the theory of Rosen & Reiter (1995). The data analysis technique in this study used multiple regression with the JASP program. Simultaneously, social comparison and perfectionism had a very significant directional correlation with body dissatisfaction (F=56,412; p<0.01). The effective contribution of the two variables is 24.5%. Partially, there is a very significant negative correlation between social comparison and body dissatisfaction (t=-6.097; p<0.01) and a very significant positive correlation between perfectionism and body dissatisfaction (t=6.782; p<0.01).Wanita pada masa emerging adulthood mengalami berbagai perubahan fisik dan psikologis serta tugas perkembangan. Adanya berbagai paparan dengan media masa, lingkungan, dan keluarga membuat wanita membandingkan dirinya sendiri dengan orang lain dan secara sosial. Melakukan perbandingan sosial dan perfeksionisme memiliki resiko membuat individu mengalami body dissatisfaction. Penelitian ini bertujuan untuk mengetahui hubungan antara social comparison dan perfeksionisme dengan body dissatisfaction. Partisipan penelitian ini adalah 350 wanita pada masa emerging adulthood diambil menggunakan Conveniance Sampling. Instrumen penelitian ini mengadaptasi dari skala the Lowa-Netherlands Comparison Orientation Measure (α=0,909), Frost Multidimensional Perfectionism Scale (α=0,857), dan skala body dissatisfaction (α=0,911) yang disusun peneliti berdasarkan teori Rosen & Reiter (1995). Teknik analisis data dalam penelitian ini menggunakan regresi ganda dengan program JASP. Secara simultan social comparison dan perfeksionisme memiliki hubungan berarah yang sangat signifikan dengan body dissatisfaction (F=56,412; p<0,01). Sumbangan efektif kedua variabel adalah 24,5%. Secara parsial dapat diketahui ada hubungan negatif yang sangat signifikan antara social comparison dengan body dissatisfaction (t=-6,097; p<0,01) dan hubungan positif yang sangat signifikan antara Perfeksionisme dengan body dissatisfaction (t=6,782; p<0,01).